Nilai Keagamaan dalam Wawacan Babad Salira - Yunidawati, Anisa (UPI, 2019)
The background of the research is the lack of public knowledge about wawacan, whereas as one of the literary works of poetry genre, wawacan consists of purwakanti (rhyme) which contained spiritual values that can be used as guidance and reflections. This research aimed to describe and analyze the transliteration of manuscripts, rhymes, and religious values in